Post a New Question

math

posted by .

2x^3+4x^2-3x^2-6x when x=3

I did2(3)^3+4(3)^2-3(3)^2-6(3)
2(27)+4(9)-3(9)-6(3)
54+36-27-18
90-27-18
63-18
45
is this correct?
Thanks

  • math -

    looks good to me.

    might have saved some work by combining 4x^2-3x^2 to be just x^2 before evaluating

    or, you could have factored it a bit:

    2x^2(x+2) - 3x(x+2) = x(2x-3)(x+2)
    = 3(3)(5) = 45

Answer This Question

First Name
School Subject
Your Answer

Related Questions

More Related Questions

Post a New Question